LOW HEAD TURBINE APPLICATION IN HYDROPOWER GENERATION : A REVIEW OF POTENTIAL AND THEORETICAL FRAMEWORK DESIGN FOR OFF-GRID ELECTRIFICATION IN SARAWAK - Nuramalina, Bohari; Abdul I. A, Rani; Mohd Shafiq, A. A.; Sherena, Sar‑ee (Universiti Malaysia Sabah, Malaysia, 2023)
This paper presents the overview study of small hydropower potential sites in Sarawak with additional review on existing project development. Sarawak is gifted with hilly areas and vast water resources which promise to give high potential in hydropower development. However, Sarawak was recorded as the lowest electrification coverage with 78.74% compares to Sabah and Peninsular Malaysia with 99.62% and 82.51%, respectively. In this research, reviews on the previous research works emphasized on low-head turbine application in Sarawak are presented. On the other hand, the potential of low-head turbine application is discussed as the pattern of remote population in Sarawak shows that most of the rural communities are located along the riverbank without elevation, thus implying the great potential for low-head turbine application to generate electricity. Moreover, most of the river in Sarawak are classified as low-pressure head with less than 10 meters and the average velocity of 1 to 2 m/s. Archimedes turbine is known as nearly zero-head turbine application, hence suitable to be installed in Sarawak particularly for remotes areas as Archimedes turbine used in low head and high flow rate application. Archimedes turbine is able to operate in less than 5 meters of water head with efficiency range in between of 60% and 80% and remains high even as available head approaches zero. The challenges and future perspectives of hydropower development in Sarawak are also discussed in this paper. Overall, this paper summarizes previous research works on hydro development in Sarawak and hence identifies the potential of low head turbine application mainly for off-grid electrification in Sarawak based on the geographical conditions as well as the topographic studies results.